4CPS-176 A systematic review of meta-analyses of the efficacy of oral antipsychotic lurasidone for the treatment of adult patients with schizophrenia. (March 2019) - Inserra, C; Zovi, A; Piacenza, M; Zerega, G
Abstract : Background: Schizophrenia is a chronic, severe and disabling mental disorder affecting more than 23 million people worldwide. The cause is multifactorial, and genetics and environmental factors are important in disease development. Patients suffer from hallucinations, delusions, disorganised thinking and behaviour, and treatment adherence is important and often difficult to obtain. Lurasidone is one of the newer approved second-generation antipsychotics orally administered for schizophrenia treatment. Lurasidone has been investigated for efficacy in six main studies, however meta-analyses are useful for clinicians and researchers to review data regarding different interventions. Meta-analyses can overcome many of the limitations of individual studies and help resolve the results of inconsistent studies. Purpose: To perform a systematic review of meta-analyses of the efficacy of lurasidone for the treatment of schizophrenia in adult patients. Material and methods: A systematic literature search was conducted (13 October 2018) using PUBMED, Embase, Metacrawler and Cochrane Library databases through the following search strategy: (lurasidone AND schizophrenia AND randomised controlled trial AND meta-analysis). When possible MeSH Terms/Emtree were used. Two authors independently conducted the literature search in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-analysis statement. Results were screened by title and abstract and then full texts were analysed. Inclusion criteria were: full-text meta-analysis of randomised controlled trials assessing the efficacy (PANSS/BPRS as outcome measure) of lurasidone versus placebo/other antipsychotic for the treatment of adult patients with schizophrenia despite the language, the country and the year of publication. Results: A total of 13 meta-analyses were found from Embase (three), PUBMED (two), Metacrawler (eight) and Cochrane Library (zero). Only one meta-analysis fitted the inclusion criteria: one was excluded as duplicate, two were abstracts and ninewere off-topic. The included meta-analysis pooled data from five similarly designed randomised controlled trials assessing the short-term efficacy of lurasidone: two phase II studies conducted between 2001 and 2004; and three phase III studies conducted between 2007 and 2010. Conclusion: According to the results, there is a significant lack of pooled data concerning the efficacy of lurasidone for schizophrenia treatment in adults. As clinicians' prescribing choice should be based on solid and accurate data, an updated meta-analysis is required to assess drug efficacy and avoiding limitations found in single studies. References and/or acknowledgements: No conflict of interest.